Inteligencia lingüística y su incidencia en el desarrollo de la lecto escritura en la Unidad Educativa José María Estrada Coello periodo 2017 - Puyutaxi Pacheco, Jessica Johanna (2017)
The research, whose scientific result supports the writing of this thesis, had the purpose of determining the incidence of linguistic intelligence in the development of reading literacy in the students of the First Year of Basic Education of the Educational Unit Jose Maria Estrada Coello, to to fulfill this purpose were selected theoretical and empirical methods of scientific research, as well as mathematical and statistical methods. The research work developed in an initial phase presented an exploratory approach, since it had as a purpose to diagnose the existing conditions in the educational unit to confront the development of linguistic intelligence and its incidence in the student writing, taking into account also the preparation of the teachers to face the process of teaching learning given, in the second phase, the system of actions was developed, taking as a point of reference the diagnosis obtained. The theoretical evaluation of this system (main scientific result), was carried out by 9 experts, agreed to accept as valid the scientific product, already mentioned. In the research, whose synthesis is public in this thesis, results were obtained, that of being taken into account by the pertinent authorities could modify the scientific problem existing in the educational institution